Catalyzing Capital Flows : Do IMF-Supported Programs Work As Commitment Devices? - Saravia, Diego (IMF Working Papers; Working Paper ;, 2003)
An objective of IMF-supported programs is to help countries improve their access to international capital markets. In this paper, we examine the issue whether IMF-supported programs influence the ability of developing country issuers to tap international bond markets and whether they improve spreads paid on the bonds issued. We find that IMF-supported programs do not provide a uniformly favorable signaling effect-that is, the mere existence of a program supported by the IMF does not act as a strong "seal of good housekeeping." Instead, the evidence is most consistent with a positive effect of IMF-supported programs when they are viewed as likely to lead to policy reform and when undertaken before economic fundamentals have deteriorated significantly. The size of the IMF-supported program matters, but the credibility of a joint commitment by the country and the IMF appears to be critical.